1998
DOI: 10.1046/j.1464-410x.1998.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave thermotherapy: a long‐term follow‐up of 67 patients from a single centre

Abstract: Objective  To determine the long‐term therapeutic value of transurethral microwave thermotherapy (TUMT) in the treatment of bladder outflow obstruction secondary to benign prostatic hyperplasia (BPH). Patients and methods  A total of 67 patients with BPH, assessed using symptom scores and measurements of urinary flow rate, underwent TUMT using the Leo Microthermer system (Laser Electro Optics Ltd, London, UK) between October 1990 and June 1992. Follow‐up information was obtained on 60 patients (90%). If they h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…20.0 (150) 9.0 (772) 5.9 (55) 5.6 (208) 13 10.1 (55) 9.7 (32) 9.1 (305) 7.9 (67) 9.6 (85) 9.5 (359) 8.4 (145) 10.9 (659) 10.5 (40) 11.4(228) 11.1 (58) 15.3 (284) 12.2 (123) 11.4(282) 11.9(175) 11.8 (113) 11.2(110) 11.9(63) 14.0 (202) 11.8 (103) 9.7 (37) 13.9 (149) 11.6 (67) 8.2 (45) 12.8 (32) 11.6 (29) 14.2 (89) 12.6 (28) 11.1 (37) 11.4 (89) 11.4 (21) of the technologies competing with TURP, long-term data are lacking. Of these competing technologies, the most extensive and longest experience has been with TUMT.…”
Section: Resultsmentioning
confidence: 99%
“…20.0 (150) 9.0 (772) 5.9 (55) 5.6 (208) 13 10.1 (55) 9.7 (32) 9.1 (305) 7.9 (67) 9.6 (85) 9.5 (359) 8.4 (145) 10.9 (659) 10.5 (40) 11.4(228) 11.1 (58) 15.3 (284) 12.2 (123) 11.4(282) 11.9(175) 11.8 (113) 11.2(110) 11.9(63) 14.0 (202) 11.8 (103) 9.7 (37) 13.9 (149) 11.6 (67) 8.2 (45) 12.8 (32) 11.6 (29) 14.2 (89) 12.6 (28) 11.1 (37) 11.4 (89) 11.4 (21) of the technologies competing with TURP, long-term data are lacking. Of these competing technologies, the most extensive and longest experience has been with TUMT.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies exist on more than 3 years of follow-up; Glass et al (9), using the Leo Microthermer system, recently reported !50% symptomatic improvement in 16 of 50 patients at 4 years, concomitant with a rate of additional treatment of 30%. Keijzers et al (10), using the Prostatron device with lower power protocol (Prostasoft 2.0), reported an overall retreatment rate of 58% within 5 years (invasive procedures in 41% and pharmacotherapy in 17%).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies are available on the short-term effects of TUMT; for review see (5). Long-term data have been less frequently reported (6)(7)(8)(9)(10). This study used the PRIMUS U R device, which works within the lower power range (11), and extends the authors' short-term data (12,13) to include a full 5-year follow-up.…”
mentioning
confidence: 98%
“…The loss to follow-up of 23% of study participants at 4 years in the LIFT study is similar to the loss to follow-up numbers seen by investigators in the Veterans Affairs Cooperative study of TURP in which 18% were lost to follow-up at the 3-year visit (18). In studies investigating TUMT loss to follow-up at equivalent time points was 30% (19) to 35% (20) while a study of TUNA reported loss to follow-up of 62% at 4 years (21). The longest prospective study for BPH surgery (TURP) followed patients for ten years, only 41% were available for follow up (22).…”
Section: Lift Study: 4-year Outcomesmentioning
confidence: 99%